Peningkatan Kinerja Pegawai Dengan Aspek Organizational Citizenship Behavior, Budaya Organisasi Dan Motivasi Di Kecamatan Sragen Kabupaten Sragen - Yustina Berti Adityas; Septiana Novita Dewi (ProBank, 2025)
The aim of this research is to empirically analyze employee performance improvement with aspects of organizational citizenship behavior, organizational culture and motivation in Sragen District, Sragen Regency. The analysis technique used is instrument testing which includes validity and reliability tests, linearity tests, regression analysis, path analysis, t test, F test, coefficient of determination test and correlation analysis. The results of the research are that Organizational Citizenship Behavior has a positive and significant effect on motivation. Organizational culture has a positive and significant effect on motivation. Organizational Citizenship Behavior has a positive and significant effect on employee performance. Organizational culture has a positive and insignificant effect on employee performance. Motivation has a positive and significant effect on employee performance. The results of the F test show that the value of F = 39.432 is significant 0.000 <0.05, so it can be concluded that together the variables Organizational Citizenship Behavior, organizational culture and motivation have a significant effect on performance. The results of calculating the total R2 value of 0.915 can be interpreted as variations in employee performance in Sragen District, Sragen Regency being explained by the variables Organizational Citizenship Behavior, organizational culture and motivation at 91.5% and the remaining 8.5% is explained by other variables outside the research model for example training and climate. Work. The most dominant path of influence on performance is the indirect path of organizational culture through motivation on performance.